PENINGKATAN PENGETAHUAN IBU-IBU PKK DALAM SWAMEDIKASI DAN ASUHAN KEPERAWATAN MANDIRI - Sikni Retno Karminingtyas; Dian Oktianti; Siti Haryani (Journal of Community Empowerment, 2024)
Self-medication is an action taken by a person to treat a disease without a doctor's prescription. Apart from self-medicating with drugs, people often treat illnesses with non-pharmacological therapy. Non-pharmacological therapy such as lifestyle modification which includes various actions that can support healing such as fever, pain and others. The aim of this service is to provide knowledge to PKK mothers in carrying out self-medication, using medication and treating minor illnesses appropriately independently, such as treating high fever in children with tepid sponges. The service activity was carried out in Siroto RT 3 RW 1, Candirejo Village and was carried out with a target group of 25 PKK women. Before counseling is carried out, screening or data collection is carried out using a questionnaire regarding knowledge of self-medication, introduction to drugs and examples as well as independent nursing care as pre-test data. After that, education was provided and data collection continued as a post-test. After obtaining the pre and post test data, proceed with data processing. Based on the evaluation before being given education, PKK mothers' understanding was in the poor category as many as 4 respondents (16.00%), sufficient as many as 14 respondents (56.00%) and good as many as 7 respondents (28.00%). Evaluation after being given education, the understanding of PKK mothers has increased, namely in the very good category of 25 respondents (100.00%).